Roger Sperry, the maverick brain scientist who was haunted by psyche - Berlucchi, Giovanni; Marzi, Carlo Alberto (Frontiers in Human Neuroscience, 2024)
This paper describes the scientific figure of Roger Sperry as a maverick researcher, an original thinker who arrived at definitive notions about the working of the brain mostly by distancing himself from the prevalent views of his peers. After solving the riddle of the functions of the corpus callosum, he won a Nobel prize in physiology or medicine for identifying the different cognitive abilities of the disconnected right and left hemispheres of the human brain. He could have won another Nobel prize for his work on the prenatal formation of behavioral neuronal networks and their growth and development after birth. In the last part of his life, he fought a courageous but inconclusive battle for demonstrating that mental and spiritual factors can direct brain activity and behavior without violating the laws of orthodox neurophysiology. Some nodal points in his scientific career and some sources of inspirations for his thinking are identified and discussed within the historical background of the neurosciences of the twentieth century.